2017
DOI: 10.1080/01616412.2017.1281198
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NMDA receptors decreased spinal microglia activation in bee venom induced acute inflammatory pain in rats

Abstract: It can be concluded that NMDA receptors take part in the mediation of spinal microglia activation in bee venom induced peripheral inflammatory pain and hyperalgesia in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…NMDA receptor activation in the spinal cord is associated with the activation of microglia and astrocytes. 45 , 46 Esketamine is a dextral isomer of ketamine with stronger analgesic effects and it strongly blocks the NMDA receptor. 23 Moreover, esketamine has some affinity for opioid receptors, and it has effects on α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and brain derived neurotrophic factor (BDNF) signaling; however, we did not find reports showing inhibition of central glial cell activation and signal pathways to explain esketamine’s analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptor activation in the spinal cord is associated with the activation of microglia and astrocytes. 45 , 46 Esketamine is a dextral isomer of ketamine with stronger analgesic effects and it strongly blocks the NMDA receptor. 23 Moreover, esketamine has some affinity for opioid receptors, and it has effects on α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and brain derived neurotrophic factor (BDNF) signaling; however, we did not find reports showing inhibition of central glial cell activation and signal pathways to explain esketamine’s analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA is widely present in the central nervous system, and the NR2B subunit is mainly distributed in the forebrain and the spinal dorsal horn, which affects the development of pain transmission and chronic pain [29,30]. It has been suggested that NMDAR2B receptors are involved in the activation of glial cells in the spinal dorsal horn of neuropathic pain models [31].…”
Section: Discussionmentioning
confidence: 99%
“…The NRS scores at 0.5 h, 4 h, 8 h, and 24 h after extubation and the cases of rescue analgesia on POD1 and POD2 in the nalbuphine combined with dexmedetomidine group were the lowest, and the QoR-40 scores were the highest ( P < 0.001), which indicated that the combination of nalbuphine and dexmedetomidine can improve the analgesic effect and the quality of postoperative recovery. The possible reasons for postoperative pain after endoscopic sinus surgery are as follows: surgical trauma causes the release of inflammatory factors and pain mediums and increases the synthesis of prostaglandins, which finally results in pain sensitization [ 16 ]; long-term sleep disorders caused by nasal diseases and the consumption of remifentanil during general anesthesia may lead to postoperative hyperalgesia [ 17 ]; and the effect of postoperative nasal packing on respiration will increase the incidence of headache and discomfort caused by brain hypoxia [ 18 ]. Nalbuphine inhibits the release of substance P from primary afferents by activating the kappa receptor in the spinal cord, thus reducing the transmission of the nerve impulses of pain to the central nervous system [ 19 ].…”
Section: Discussionmentioning
confidence: 99%